Evolution of Participative Structures within the Particular Church since the Time of Vatican II - Lusabe, Lennoxie N. (Studia canonica, 2018)
The author considers the evolution of five participative structures from Vatican Council II to the present. He contends that a good analysis, critique, and interpretation of the law must consider the context in which that law emerges and operates. He considers the development of five selected structures in the particular Church: the diocesan synod, the diocesan finance council, the presbyteral council, the college of consultors, and the diocesan pastoral council.